Cultivation of Flammulina velutipes (Golden needle mushroom/Enokitake) on various agroresidues / Nooraishah binti Harith - Harith, Nooraishah (2014)
Sawdust and rice bran are common commercially used fruiting substrate components for the cultivation of Flammulina velutipes, or known as ‘golden needle mushroom’ in Malaysia. Due to the declining of sawdust supply, and the abundance of lignocellulosic agroresidues in Malaysia, hence, this study was carried out to investigate the possibility of using palm oil wastes; such as empty fruit bunches (EFB), palm pressed fiber (PPF), and paddy straw (PS) from rice plantation, as base carbon-sources in fruiting substrate used as either singular or in combination with different agroresidues. The percentage of rice bran (RB) and spent yeast (SY) used as the nitrogen-sources supplemented were also investigated. Mycelium growth and density, yield of mushroom and biological efficiency (BE) were the parameters determined to evaluate singular and different combination of substrates tested. For the improvement of F. velutipes inoculum addition of growth hormone used in this study consisting of β-indole acetic acid (IAA) combined with 6-benzylaminopurine (BAP) at a concentration of 0.5 mg/L each enhanced mycelial growth rate at 10.53 mm/day compared to non-supplemented malt extract agar (MEA) media (7.83 mm/day). All the agro-residues tested showed good potential to be used as fruiting substrates for the cultivation of F. velutipes based on mycelial and basidiocarp yield. For singular substrate, PPF (100) and EFB (100) showed higher mean radial growth rates of mycelium of 6.64 and 6.17 mm/day respectively, compared to other agroresidues. Among the formulations, combination of substrates, SD+PPF (75:25), PS+PPF (50:50) and SD+PS (50:50) showed higher mycelial growth rates of 7.20, 6.84 and 6.78 mm/day respectively. In terms of basidiocarp yield, EFB+PS (75:25), PS+PPF (50:50), and PPF (100) gave highest BE of 185.09, 150.89, and 129.06% respectively. Nitrogen supplementation with rice bran and spent yeast at levels of 5.0 – 20.0% concentrations showed no significant effects based on mycelial growth rate, basidiocarp yield and BE. These fruiting substrate formulations would be a good alternative for the growers of F. velutipes since they are easily available in abundance and low-cost.